Social Engineering Melalui Hukum Pidana: Efektivitas UU ITE Dalam Mengubah Perilaku Komunikasi Digital Masyarakat Indonesia - Muhamad Abdul Kholik; Dewi Sulastri (Ius Poenale, 2025)
The rapid expansion of digital communication in Indonesia, with 220 million internet users in 2025, has been accompanied by a surge in hoaxes and hate speech, including 103,000 negative contents during the 2024 election, prompting the need for adaptive criminal law as a tool of social engineering. This study examines Law No. 1 of 2024 as an instrument of social engineering in Roscoe Pound’s sense to shape digital communication behavior, using a normative legal method that integrates statutory analysis, conceptual theory, purposive cases, and comprehensive secondary data from court decisions and state reports. The findings show that revisions to key provisions of the ITE Law reduced hoaxes by 28 percent, increased verification behavior among 68 percent of users, and enabled the removal of 15,000 harmful contents, but persistent problems remain, including ambiguous norms, low digital literacy, enforcement disparities, and self-censorship. The study concludes that while the ITE Law is strategically important, it requires further reform to shift from a punitive to a transformative approach, and it recommends clearer norms, mandatory mediation, strengthened digital literacy, specialized cyber courts, and independent oversight to support a democratic and Pancasila-based digital ecosystem.